2003
DOI: 10.1021/bi034661v
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Origin of the Slow-Binding Inhibition of HCV NS3 Serine Protease by a Novel Substrate Based Inhibitor

Abstract: Indandiones were identified as a novel class of small molecule inhibitors of hepatitis C virus NS3 serine protease from high throughput screening. We further studied the structure activity relationships and the mechanisms of inhibition for this class of compounds. Our studies revealed two similar, yet different, mechanisms accounting for the apparent indandione inhibition of HCV NS3 protease. In one case, the apparent inhibition results from the chemical breakdown of the parent compound and the subsequent redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We also like to add a short preincubation step of compound with enzyme or receptor prior to the initiation of the reaction to allow for slow-binding inhibitors, which require a conformational change, in order to form a tight complex with the target. [114][115][116][117] Longer incubation steps can also add significant amounts of plate processing time in HTS automation because incubation time often represents the rate-limiting step in the HTS process. Reaction rates can be increased by increasing the enzyme concentration or temperature, and, in this fashion, incubation times can be reduced.…”
Section: Incubation Timesmentioning
confidence: 99%
“…We also like to add a short preincubation step of compound with enzyme or receptor prior to the initiation of the reaction to allow for slow-binding inhibitors, which require a conformational change, in order to form a tight complex with the target. [114][115][116][117] Longer incubation steps can also add significant amounts of plate processing time in HTS automation because incubation time often represents the rate-limiting step in the HTS process. Reaction rates can be increased by increasing the enzyme concentration or temperature, and, in this fashion, incubation times can be reduced.…”
Section: Incubation Timesmentioning
confidence: 99%
“…Indan-1,3-diones derivatives have been specifically associated with antiviral activity. Studies have indicated efficient action of indan-1,3-diones against the enzyme integrase of the HIV-1 virus [36]; against the structure of human papillomavirus (HPV) [3739]; and also against the Hepatitis C virus (HCV) protease [40], and recently for WNV protease [41]. Eugenol has been tested against the Herpes virus (HSV), HSV-1 (five viral isolates) and HSV-2 (five viral isolates), providing complete protection against one isolate of each type, HSV-1 and 2, and protection between 16.5% and 87.7% for the remaining isolates [2123].…”
Section: Introductionmentioning
confidence: 99%
“…(b) The molecule offers wide scope for the study of physiochemical properties such as 1,3-indandione tautomerism, dual reactivity, electrochemical redox properties, unique property of polycrystalline films, and quantum mechanical calculations, and so forth [3,4]. (c) A wide range of biological properties covering antimicrobial, antitumor, anti-inflammatory, antiviral, antihepatitis, anticoagulant, rodenticidal, herbicidal, and insecticidal properties were associated with indane-1,3-dione derivatives [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%